2017
DOI: 10.1177/1065912917698045
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Genes, Personality Traits, and Political Interest

Abstract: Political interest is one of the strongest predictors of individual political engagement, but little is known about the origins of this political orientation. The goal of this paper is to clarify the role that biological and psychological factors play in the formation of political interest. A series of recent studies in genetics have illustrated that political interest is heritable, and a series of recent studies in political science and psychology have demonstrated that personality traits, many of which are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 54 publications
3
44
2
Order By: Relevance
“…The only Big Five trait that was an important correlate of political engagement and interest in our study was openness, which has been a fairly consistent predictor of interest in politics and participation across different studies. 14,25,31 Our results regarding the genetic overlap between openness and political interest are nearly identical to previous estimates.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The only Big Five trait that was an important correlate of political engagement and interest in our study was openness, which has been a fairly consistent predictor of interest in politics and participation across different studies. 14,25,31 Our results regarding the genetic overlap between openness and political interest are nearly identical to previous estimates.…”
Section: Resultssupporting
confidence: 88%
“…Finally, we note that while Weinschenk and Dawes 25 found that extraversion, conscientiousness, openness, and neuroticism were moderately correlated with political interest in U.S. samples, we find that among the Big Five traits, only openness shows a moderate correlation with political interest in our sample. Since the correlations for all of the psychological traits besides cognitive ability and openness are small in magnitude (and many of them are not statistically significant), making it difficult to decompose their covariance without an extremely large sample, we exclude them from the bivariate analysis.…”
Section: Analysis and Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…Again, the answer is no. The view that genes play a significant role in human personality is held by Weinschenk & Dawes (2017) in their study of the relationship between genes, personality traits, and political interest which affirmed that genetic factors account for substantial correlation between personality traits and interest in politics. The pervasive influence of the human gene on behaviour does not indicate that a single or several genes can make us react in a specific way to an external stimulus or that behaviour can be inherited.…”
Section: Deconstructing the Role Of Genes In Human Personalitymentioning
confidence: 99%